Essays in applied demand and production analysis - Zereyesus, Yacob Abrehe (Kansas State University, 2010)
This dissertation is composed of two essays in applied microeconomics. Using farm level data, the first essay applied nonparametric methods to test the adherence of individual farm’s production choices to profit maximization objective. Results indicate that none of the farms consistently satisfy the joint hypothesis of profit maximization. The study took into account the uncertainty prevalent in agricultural production by systematically modeling the optimization behavior of farms. Departures of observed data of individual farms from profit maximization objectives were attributed more due to stochastic influences caused by output production decisions than input use decisions. Results also support the existence of technological progress during the study period for Kansas farms. At an alpha level of 5%, assuming both input and output quantities as stochastic, only 5.3% of the farms violated the joint hypothesis of profit maximization with standard error exceeding 10%. Whereas when only input quantities are considered stochastic, a total of 71.73% and 2.09% of the farms had minimum standard errors of greater than 10% and 20% respectively required for the joint profit maximization hypothesis to hold. When only output quantity measurements were assumed as stochastic, a total of 80.10 % and 18.84 % of the farms had minimum standard errors of greater than 10% and 20% respectively required for the profit maximization hypothesis to hold. The second essay examines the demand for alcoholic beverages (beer, wine and distilled spirits) for the U.S. using time series data from 1979-2006. The estimation is done using an error correction form of the Almost Ideal Demand System . Results indicate that there is a significant difference between short run and long run elasticity estimates. The paper addresses the exogeneity of log of prices and log of real expenditures. For the beer and wine equations, the hypothesis of joint exogeneity of price index and real expenditure cannot be rejected at all the conventional levels of significance. For the spirits equation, the tests strongly reject the simultaneous exogeneity of price index and real expenditure. When independently tested, price index appears to be endogenous variable where as real expenditure seems exogenous variable. Based on these results, the real expenditure was considered as an exogenous variable, where as the price index for spirits as an endogenous variable.
Keywords: Profit maximization; Non parametric; Stochastic; Alcoholic beverages; Error correction; Almost Ideal Demand System (AIDS); Economics, Agricultural (0503)